HPLC-DAD and UHPLC/QTOF-MS Analysis of Polyphenols in Extracts of the African Species Combretum padoides, C. zeyheri and C. psidioides Related to Their Antimycobacterial Activity - Pia Fyhrquist; Enass Y. A. Salih; Satu Helenius; Into Laakso; Riitta Julkunen-Tiitto (MDPI AG, 2020)
Combretum padoides Engl. & Diels, C. psidioides Welv. and C. zeyheri Sond. are used for the treatment of infections and tuberculosis related symptoms in African traditional medicine. In order to verify these uses, extracts were screened for their growth inhibitory effects against M. smegmatis ATCC 14468. Ultra-high pressure liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UHPLC/QTOF-MS) and GC-MS were used to investigate the polyphenolic composition in the active extracts. The lowest minimum inhibitory concentration (MIC), 625 µg/mL, was shown by a methanol extract of the stem bark of C. psidioides. A butanol extract of C. psidioides gave large inhibition zone diameters (IZD 21 mm) and inhibited 84% of the mycobacterial growth at 312 µg/mL. Combretastatin B-2 and dihydrostilbene derivatives were present in the methanol extract of C. psidioides, whereas the butanol extract of this species contained punicalagin, corilagin, and sanguiin H-4. Methanol and butanol extracts of the stem bark of C. padoides gave large inhibition zone diameters (IZD 26.5 mm) and MIC values of 1250 and 2500 µg/mL, respectively. C. padoides contained an ellagitannin with a mass identical to punicalagin ([M-H]− 1083.0587) and a corilagin like derivative ([M-H]− 633.0750) as well as ellagic acid arabinoside and methyl ellagic acid xyloside. A butanol extract of the roots of C. zeyheri showed mild antimycobacterial activity and contained a gallotannin at m/z [M-H]− 647.0894 as the main compound along with punicalagin and three unknown ellagitannins at m/z [M-H]− 763.0788, 765.0566, and 817.4212. Our results indicate that the studied species of Combretum contain phenolic and polyphenolic compounds with possible potential as leads for antimycobacterial drugs or as adjuvants for conventional anti-TB drugs.